The Shape of The Earth in The Perspective of Islam and Hinduism (Departement of Comparative Study of Religions, 2024)
This research intends to know the shape of the earth through the perspective of Islam and Hinduism. With descriptive, analysis and comparative methods, the researcher produced three important conclusions. Firstly, the two scriptures agreed that the phenomenon of day and night is caused by sunlight. Rationally this phenomenon will not happen except by the globe earth. Secondly, in the perspective of Islam, it is not mentioned clearly about the shape of the earth but differs in the perspective of Hinduism which mentioned it clearly. This matter causes different views and interpretations. Thirdly, Al-Biruni that represent the Muslim scholar and Aryabhata represent Hindu, in study the shape of the earth, the both did their research by using the concept of a globe earth and the results were still in use today. Knowing more details, the research on the shape of the earth becomes very interesting.